Near-ideal van der Waals rectifiers based on all-two-dimensional Schottky junctions - Zhang, Xiankun; Liu, Baishan; Gao, Li; Yu, Huihui; Liu, Xiaozhi; Du, Junli; Xiao, Jiankun; Liu, Yihe; Gu, Lin; Liao, Qingliang; Kang, Zhuo; Zhang, Zheng; et al. (Nature communications, 2021)
The applications of any two-dimensional (2D) semiconductor devices cannot bypass the control of metal-semiconductor interfaces, which can be severely affected by complex Fermi pinning effects and defect states. Here, we report a near-ideal rectifier in the all-2D Schottky junctions composed of the 2D metal 1 T′-MoTe 2 and the semiconducting monolayer MoS 2 . We show that the van der Waals integration of the two 2D materials can efficiently address the severe Fermi pinning effect generated by conventional metals, leading to increased Schottky barrier height. Furthermore, by healing original atom-vacancies and reducing the intrinsic defect doping in MoS 2 , the Schottky barrier width can be effectively enlarged by 59%. The 1 T′-MoTe 2 /healed-MoS 2 rectifier exhibits a near-unity ideality factor of ~1.6, a rectifying ratio of >5 × 10 5 , and high external quantum efficiency exceeding 20%. Finally, we generalize the barrier optimization strategy to other Schottky junctions, defining an alternative solution to enhance the performance of 2D-material-based electronic devices. Here, a defect healing method is used to tune the height and width of the Schottky barrier at the interface between 2D metals and 2D semiconductors, leading to the realization of van der Waals rectifiers with enhanced performance.